THE VERNACULARITY IN THE TAFSÄªRIYAH TRANSLATION OF NADOMAN NURUL HIKMAH - Muchtar, Ahmad Rifqi; Luthfiana, Mariya (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
The vernacularity of the poetic translation of the Qur'an Nadoman Nurul Hikmah by Hidayat Suryalaga lies in its peculiarity in using the language and rules of Sundanese poetry of praise. This paper aims to explain the form of vernacularity in the translation of Nadoman Nurul Hikmah's interpretation by H. R. Hidayat Suryalaga. This article uses descriptive methods and content analysis, thus concluding that the aspect of nadoman content or the meaning of the verses in Nadoman Nurul Hikmah is far more accurately called a translation of tafsiriyah al-Qur'an than it is called poetic interpretation of the Qur'an. H. R. Hidayat Suryalaga, in Nadoman Nurul Hikmah, does not at all refer to the Arabic translation or interpretation in each stanza. H. R. Hidayat Suryalaga did not use the verse editor as a source, but he tried to provide his interpretation. Meanwhile, in Nadoman, Nurul Hikmah does the loose and contextual translation. The contextualization of the verses of the Qur'an gives the impression to the readers (singers) of Nadoman that Nadoman Nurul Hikmah can be enjoyed by anyone who is by the spirit of the times.